#### Answer

x-intercept = -2
y-intercept = 3
Refer to the image below for the graph.

#### Work Step by Step

Write the equation in $Ax +By=C$ form.
This will make solving for the intercepts a lot easier.
The given equation can be rewritten as:
$\dfrac{1}{2}x-\dfrac{1}{3}y+1=0
\\\dfrac{1}{2}x-\dfrac{1}{3}y+1-1=0-1
\\\dfrac{1}{2}x-\dfrac{1}{3}y=-1
\\6\left(\dfrac{1}{2}x-\dfrac{1}{3}y\right)=-1(6)
\\6(\frac{1}{2}x) - 6(\frac{1}{3}y)=6
\\3x-2y=-6$
To find the $x$ intercept, set $y=0$ then solve for $x$ to obtain:
$3x-2y=-6
\\3x-2(0) = -6
\\3x=-6
\\\dfrac{3x}{3}=\dfrac{-6}{3}
\\x=-2$
The x-intercept is $-2$.
To find the $y$ intercept, set $x=0$ then solve for $y$ to obtain:
$3x-2y=-6
\\3(0)-2y = -6
\\-2y=-6
\\\dfrac{-2y}{-2}=\dfrac{-6}{-2}
\\y=3$
The y-intercept is $3$.
To draw the graph of the equation, plot the x-intercept point $(-2, 0)$ and the y-intercept point $(0, 3)$ and connect them using a straight line.
(refer to the attached image in the answer part above)